Exports, education, and growth in Malaysia - Yusoff, Mohammed (2008)
This paper examines the causal link between exports and education expenditure in Malaysia’s economic development using the cointegration technique, VECM and Granger causality test. The results suggest that the variables: GDP, exports, and education expenditure are cointegrated. The estimated long-run relationship shows that both exports and education expenditure could explain the variation in real GDP where both are significant at one percent level. The Granger causality test indicates that both the exports and education expenditure cause economic growth where it is significant at one percent level. These imply that the Malaysian export-oriented and education development strategy have played a very important role in the development of Malaysian economy. Keywords: Exports, education, growth, causality